Morphosemantic Analysis of -ITIS Forms in Medical Language - Pacak, M. G.; Norton, L. M.; Dunham, G. S. (Methods of Information in Medicine, 1980)
This paper describes an automated procedure for morphosemantic analysis and semantic interpretation of medical compound word forms ending in -ITIS. The requirements for morphosemantic analysis of -ITIS forms include : a) semantic classification of morphosemantic constituents forming -ITIS word forms, b) establishment of morphosemantic distribution patterns occurring in -ITIS forms, c) preparation of paraphrasing rules.
Keywords: Medical Language; Morphosemantics; Automated Compound Word Segmentation; Paraphrasing